2022
DOI: 10.3389/fpls.2022.887226
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Difference of Interactive Effect Between Temperature and Daylength on Ginkgo Budburst

Abstract: Climate warming-induced shifts in spring phenology have substantially affected the structure and function of terrestrial ecosystems and global biogeochemical cycles. Spring phenology is primarily triggered by spring temperature and is also affected by daylength and winter chilling, yet the relative importance of these cues across spatial gradients remains poorly understood. Here, we conducted a manipulative experiment with two daylength and three temperature treatments to investigate spatial differences in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Chilling and photoperiod limitation were nonlinearly correlated with MAT, and positively linearly correlated with MAP, consistent with the environmental gradients in phenological responsiveness. Previous studies have indicated that photoperiod limitation on spring leaf‐out increases with MAT, because decreases in chilling accumulation toward warmer regions will lead to higher photoperiod sensitivity (Zhang et al ., 2007; Zohner et al ., 2016; Wu et al ., 2022b). Our study now provides evidence that photoperiod limitation may also increase toward cold regions, where temperatures are regularly below the effective chilling temperature range.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Chilling and photoperiod limitation were nonlinearly correlated with MAT, and positively linearly correlated with MAP, consistent with the environmental gradients in phenological responsiveness. Previous studies have indicated that photoperiod limitation on spring leaf‐out increases with MAT, because decreases in chilling accumulation toward warmer regions will lead to higher photoperiod sensitivity (Zhang et al ., 2007; Zohner et al ., 2016; Wu et al ., 2022b). Our study now provides evidence that photoperiod limitation may also increase toward cold regions, where temperatures are regularly below the effective chilling temperature range.…”
Section: Discussionmentioning
confidence: 99%
“…In warm areas, the higher risk of late spring frosts (Zohner et al ., 2020a) may contribute to a decrease in RSP as a strategy to mitigate potential frost damage. To achieve this, trees adapted to warmer climates may exhibit greater sensitivity to photoperiod limitation, resulting in a lower RSP (Zohner et al ., 2016; Wu et al ., 2022b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations